Case Study on Latest Methods and Materials That Can Be Used for Construction of JUHU Aerodrome: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There are large number of airports in India, of which some are not in service or in use. These airports can be repaired or reconstructed. These airports if got under rehabilitation then the burden on the running airports can be reduced. New paths or new ways can be found out and public transport and materials transport can be distinguished clearly. Management of crowd and cargos in overcrowded metropolitan cities like Mumbai, Delhi, Kolkata and Chennai can be done in more sophisticated manner. Hence, the obstructions under development of these cities can be reduced. So, in this case we have considered Mumbai city as an example of overcrowding and larger number of cargo of materials to be supplied. In CSI Airport, out of two only one runway is working therefore, numbers of flights per day are increased on that pavement increasing the probability of danger of accidents. So, to minimize the problems Juhu aerodrome in Mumbai can be rehabilitated. In this paper our aim is to find out and discuss the latest construction techniques, materials and methods like piezo-electric pavement for landing so that the construction of runway will become safer, faster, less costly and eco-friendly